2019
DOI: 10.3390/ijms20205038
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen-Loaded Hyaluronic Acid Nanofibrous Membranes for Prevention of Postoperative Tendon Adhesion through Reduction of Inflammation

Abstract: A desirable multi-functional nanofibrous membrane (NFM) for prevention of postoperative tendon adhesion should be endowed with abilities to prevent fibroblast attachment and penetration and exert anti-inflammation effects. To meet this need, hyaluronic acid (HA)/ibuprofen (IBU) (HAI) NFMs were prepared by electrospinning, followed by dual ionic crosslinking with FeCl3 (HAIF NFMs) and covalent crosslinking with 1,4-butanediol diglycidyl ether (BDDE) to produce HAIFB NFMs. It is expected that the multi-functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…However, current innovations cannot completely restrict adhesion during extrinsic healing. Furthermore, biochemical drugs applied on membranes (such as ibuprofen, microRNAs, basic fibroblast growth factor, and silver nanoparticles) cause side effects or reduce the quality of tendon healing (Shalumon et al, 2018;Zhou et al, 2018;Chen et al, 2019;Zhao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, current innovations cannot completely restrict adhesion during extrinsic healing. Furthermore, biochemical drugs applied on membranes (such as ibuprofen, microRNAs, basic fibroblast growth factor, and silver nanoparticles) cause side effects or reduce the quality of tendon healing (Shalumon et al, 2018;Zhou et al, 2018;Chen et al, 2019;Zhao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Focal adhesions were fewer in number and smaller in size, and the vinculin and vimentin staining intensities were lower in the HA group than in the NS group ( Figure 5 ). Similarly, Chen et al have recently developed HA-based multi-functional nanofibrous membranes (NFMs) loaded with ibuprofen to mimic the anti-adhesive function of the native tendon sheath, as well as to induce anti-inflammatory responses at the tenorrhaphy sites [ 50 ]. They successfully demonstrated that ibuprofen-loaded HA-NFM could minimize the cell attachment, as evidenced by the minimal expression of vinculin and restricted cytoskeleton organization, resulting in the prevention of cell penetration and tendon adhesion formation during tendon healing.…”
Section: Discussionmentioning
confidence: 99%
“…The HAIFB NFMs reduced inflammation, prevented cell attachment and infiltration, and reduced and formed tissue adhesions (Figure 8B,C). [ 206 ] IBU was assessed as a nonepitope of macrophages in tendon tissue, and the spacing between the barrier and tendon can be distinguished.…”
Section: Inhibitory Biological Process For Anti‐adhesionmentioning
confidence: 99%